RESILIENSI DENGAN SELF-COMPASSION PADA FAMILY CAREGIVER ORANG DENGAN SKIZOFRENIA (ODS) - Pratiwi, Anjani Claudia; Mardhiyah, Sayang Ajeng (Program Studi Psikologi Fakultas Kedokteran Universitas Sriwijaya, 2019)
This research aims to know the relationship between resilience with self-compassion of family caregiver people with schizophrenia. This hypothesis was there is relationship between resilience with self-compassion of family caregiver people with schizophrenia. The population of the study was a family caregiver people with schizophrenia at RS. Ernaldi Bahar, South Sumatera. The subject was 100 person and for tryout was 30 person. This study used insidental sampling technique. Resilience and self-compassion was measured by the scale of component resilience from grotberg (2003) with refererence to component from Grotberg (2003) and component self-compassion from Neff (2003). Data analysis using simple corelation Person’s Product Moment. The result of the correlation sperman showed that there is relationship between resilience with self-compassion of family caregiver people with schizophrenia with value of r= 0,921, and p=0,000 (p<0,05). It show that resilience has very strong and significant relationship with self-compassion. Thus the hypothesis is accepted.